Survey of Campus Law Enforcement Agencies, 1995: (United States) ([Verlag nicht ermittelbar], 1997)
In 1995, to determine the nature of law enforcement services provided on campus, the Bureau of Justice Statistics (BJS) surveyed four-year institutions of higher education in the United States with 2,500 or more students. This survey describes nearly 600 of these campus law enforcement agencies in terms of their personnel, expenditures and pay, operations, equipment, computers and information systems, policies, and special programs. The survey was based on the BJS Law Enforcement Management and Administrative Statistics (LEMAS) program, which collected similar data from a national sample of state and local law enforcement agencies.